Effects of Inclusion Levels of Discarded Corn Grain on Growth Performance, Edible Portions and Economic Response in Broilers - Elvir, Elmer Modesto; Vega, Andrés Sebastian; Martínez, Yordan; Valdivié, Manuel; Rodríguez, Roman (International Journal of Poultry Science, 2020)
Background and Objective: The challenge for nutritionists is to formulate diets with available alternative sources to reduce production costs, without depressing animal performance. The objective of this study was to evaluate the effects of inclusion levels of discarded corn grain on growth performance, edible portions and economic response in broilers. Materials and Methods: A total of 1,200 one-day-old Ross 308® broilers were distributed in a completely randomized design with four treatments and six replications. Diets with inclusion levels of 0, 100, 200 and 300 g kg–1 of discarded corn grain were formulated. Results: Throughout the experimental stage, the inclusion level of 300 g kg–1 of discarded corn grain improved body weight and feed conversion ratio (starter and grower), without affecting feed intake (except 0-32 days). Likewise, this inclusion level (300 g kg–1) improved the viability in the grower phase compared to the control. Dietary use of discarded corn grain did not change (p<0.05) the relative weight of the carcass, leg, liver and heart, however, the inclusion of 200 g kg–1 of discarded corn grain improved the relative weight of the breast and 300 g kg–1 increased the relative weight of abdominal fat and gizzard. Likewise, a higher inclusion of discarded corn grain in broiler diets decreased the feed cost, the cost to produce one kg of body weight, carcass and breast. Conclusion: The inclusion level of 300 g kg–1 of discarded corn grain in broiler diets promoted a better productive and economic response; however, the inclusion of 200 g kg–1 improved the breast yield, without affecting the other edible portions.